فتح الذرائع وتطبيقاتها الفقهية في تقنيات الإنجاب المساعدة (ART) : Fath Al-Dharāʾiʿ (Facilitating the Means) and its Jurisprudential Applications in Assisted Reproductive Technology (Art) - Bilal Hussain; Dr. Majdah Binti Zawawi (Al Manhal Research Journal, 2025)
The doctrine of Fath al-Dharāʾiʿ (facilitating the means) stands as a pivotal legal principle in Islamic jurisprudence, promoting the pursuit of benefits through permissible means. For instance, classical jurists have applied this principle to permit the use of new medical treatments and surgical techniques to save lives and improve health, even if such methods were not explicitly mentioned in classical texts. This study rigorously explores the application of Fath al-Dharāʾiʿ in the context of Assisted Reproductive Technology (ART) within Islamic jurisdictions. ART, a pivotal medical advancement, brings substantial societal benefits alongside nuanced implications. This study examines how Fath al-Dharāʾiʿ serves as a legal foundation for governing ART within Islamic jurisdictions, exploring its role in shaping ART policies under Shariah law. Utilising qualitative research methods, the study draws upon Islamic legal texts, scholarly articles, and fatwas concerning Fath al-Dharāʾiʿ. It contributes essential insights into the application of ART within Islamic legal frameworks, particularly in Muslim-majority regions. The findings provide valuable guidance for policymakers and researchers, facilitating informed analysis of ART-related regulations in light of both classical jurisprudence and contemporary societal dynamics.